2016
DOI: 10.3402/mehd.v27.30312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fragmentedLactobacillus amylovorusCP1563 on lipid metabolism in overweight and mildly obese individuals: a randomized controlled trial

Abstract: BackgroundPreviously, we showed that fragmented Lactobacillus amylovorus CP1563 (CP1563) functions as a dual agonist of peroxisome proliferator-activated receptor α and γ in vitro and in vivo.ObjectiveHere, we examined the safety and effect of CP1563 ingestion on body fat in obese class I participants in a double-blinded, placebo-controlled, randomized clinical trial (RCT).DesignIn the RCT, 200 participants with a body mass index (BMI) of 25–30 kg/m2 consumed test beverages with or without 200 mg of CP1563 dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…PPAR‐α has been used as a target of gene therapy for obesity and dyslipidemia, especially for synthetic agonists such as fibrates . However, emerging studies suggest that pre‐ and probiotics could act as effective PPAR‐α agonists . A recent study showed that the administration of PPAR‐α ‐agonistic probiotics L. amylovorus CP1563 for 12 weeks in the overweight and mildly obese individuals improved the adiposity and lipid and glucose metabolism with no adverse effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR‐α has been used as a target of gene therapy for obesity and dyslipidemia, especially for synthetic agonists such as fibrates . However, emerging studies suggest that pre‐ and probiotics could act as effective PPAR‐α agonists . A recent study showed that the administration of PPAR‐α ‐agonistic probiotics L. amylovorus CP1563 for 12 weeks in the overweight and mildly obese individuals improved the adiposity and lipid and glucose metabolism with no adverse effects .…”
Section: Discussionmentioning
confidence: 99%
“…that pre-and probiotics could act as effective PPAR-␣ agonists [7,8]. A recent study showed that the administration of PPAR-␣-agonistic probiotics L. amylovorus CP1563 for 12 weeks in the overweight and mildly obese individuals improved the adiposity and lipid and glucose metabolism with no adverse effects [7].…”
Section: Discussionmentioning
confidence: 99%
“…1). Of the 26 articles which were full text screened, a total of 11 articles did not meet the criteria of inclusion either because the independent effects of probiotics on outcomes were not possible to estimate (23)(24)(25)(26)(27)(28)(29)(30), the probiotic species were not defined (31) or the patients had undergone gastric bypass (32) or lacked sufficient information on the outcomes of interest (33). Finally, 15 articles were included in the systematic review and meta-analysis (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Study Selectionmentioning
confidence: 99%
“…For instance, Sugawara et al, (2016) investigated the role of a heattreated strain of Lactobacillus gasseri given daily in a beverage to get 10 10 cells per day, to a group of adults in a randomized placebo controlled study design, and noted the benefits as preventing the degeneration of quality of life and the occurrence of lifestyle-related diseases. In another randomized control trial on obese human subjects where a strain of heat-killed Lactobacillus amylovorus was given on a daily basis in a beverage for 12 weeks, a reduction of obesity was noted (Nakamura et al, 2016). With such findings, the impact of heat-killed microbes in cooked fermented products such as 'hoppers', 'thosai' and 'idli' are yet to be deciphered.…”
Section: Non-viable Cells Serving As Probiotics In Cooked Fermented Fmentioning
confidence: 99%